Discourse Analysis of a News Text Using Cohesion and Ethnography of Speaking Theories - Angela Audreylia Sabrina; Gunawan, Salsabilla Maharani Mutiara; Pujiati, Hanip (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2023)
The purpose of this study was to undertake a thorough study of a news article entitled